2020
DOI: 10.2217/fon-2020-0213
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Diagnostic Performance of FNA-Tg in Detecting Lymph Nodes Metastases from Papillary Thyroid Cancer

Abstract: Background: Thyroglobulin washout of fine needle aspiration (FNA-Tg) has proved to be useful in detecting lymph node metastases from papillary thyroid cancer; however, the influences of thyroid gland, Hashimoto thyroiditis, serum thyroglobulin (Tg) and anti-TG antibody on the diagnostic performance of FNA-Tg are controversial. Patients & methods: We retrospectively collected the FNA-Tg results of 176 preoperative or postoperative patients (356 lymph nodes) who finally were diagnosed with papillary thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
6
16
1
Order By: Relevance
“…LNs in the central region are more easily affected by blood contamination by circulating Tg at the time of sampling, or Tg leakage into the LN by lymph vessel draining. 7 , 25 , 26 In the present study, only serum TgAb levels correlated negatively with FNA-Tg in the central LN group. It is quite possible that underestimation of the FNA-Tg concentration occurs, to some degree, in the presence of circulating TgAb in the central LN region but not in the lateral region.…”
Section: Discussionsupporting
confidence: 42%
“…LNs in the central region are more easily affected by blood contamination by circulating Tg at the time of sampling, or Tg leakage into the LN by lymph vessel draining. 7 , 25 , 26 In the present study, only serum TgAb levels correlated negatively with FNA-Tg in the central LN group. It is quite possible that underestimation of the FNA-Tg concentration occurs, to some degree, in the presence of circulating TgAb in the central LN region but not in the lateral region.…”
Section: Discussionsupporting
confidence: 42%
“…16 However, Wang noted that sTgAb did not affect the FNA-Tg measurements when diagnosing CLNM. 20 In this study, we found that sTgAb can slightly influence the FNA-Tg level, but cannot alter the result of the diagnosis of FNA-Tg.…”
Section: Diagnostic Performance Of Different Proceduresmentioning
confidence: 51%
“…The superior sensitivity and excellent negative predictive values support its routine use as guidance for lateral neck dissection. Because the level of FNA-Tg in the central compartment was easier to be by affected blood contamination or Tg leakage than that in the lateral compartment 4 , 5 , the additional diagnostic value of FNA-Tg is limited in central neck dissection planning. It is of note that, as compared to the absolute value, no diagnostic advantage was found for the difference or ratio between FNA-Tg and serum Tg.…”
Section: Presentmentioning
confidence: 99%